Nifedipine Increases Iron Content in WKPT-0293 Cl.2 Cells via Up-Regulating Iron Influx Proteins - Yu, Shuang-Shuang; Jiang, Li-Rong; Ling, Yan; Qian, Zhong-Ming; Zhou, Yu-Fu; Li, Juan; Ke, Ya (Frontiers in Pharmacology, 2017)
Nifedipine was reported to enhance urinary iron excretion in iron overloaded mice. However, it remains unknown how nifedipine stimulates urinary iron excretion in the kidney. We speculated that nifedipine might inhibit the TfR1/ DMT1 (transferrin receptor 1/ divalent metal transporter1)-mediated iron uptake by proximal tubule cells in addition to blocking L-type Ca2+ channels, leading to an increase in iron in lumen-fluid and then urinary iron excretion. To test this hypothesis, we investigated the effects of nifedipine on iron content and expression of TfR1, DMT1 and ferroportin1 (Fpn1) in WKPT-0293 Cl.2 cells of the S1 segment of the proximal tubule in rats, using a graphite furnace atomic absorption spectrophotometer and Western blot analysis, respectively. We demonstrated for the first time that nifedipine significantly enhanced iron content as well as TfR1 and DMT1 expression and had no effect on Fpn1 levels in the cells. We also found that ferric ammonium citrate (FAC) decreased TfR1 levels, increased Fpn1 expression and had no effect on DMT1 content, while co-treatment with nifedipine and FAC increase TfR1 and DMT1 expression and also had no effect on Fpn1 levels. These findings suggest that the nifedipine-induced increase in cell iron may mainly be due to the corresponding increase in TfR1 and DMT1 expression and also imply that the effects of nifedipine on iron transport in proximal tubule cells can not explain the increase in urinary iron excretion.